Long-Term Efficacy of Low-Intensity Single Donor Fecal Microbiota Transplantation in Ulcerative Colitis and Outcome-Specific Gut Bacteria - Ren, Rongrong; Gao, Xuefeng; Shi, Yichao; Li, Jianfeng; Peng, Lihua; Sun, Gang; Wang, Zikai; Yan, Bin; Zhi, Junli; Yang, Yunsheng (Frontiers in Microbiology, 2021)
Aims: To assess the long-term efficacy and safety of single-donor, low-intensity fecal microbiota transplantation (FMT) in treating ulcerative colitis (UC), and to identify the outcome-specific gut bacteria. Design: Thirty-one patients with active UC (Mayo scores ≥ 3) were recruited, and all received FMT twice, at the start of the study and 2∼3 months later, respectively, with a single donor and a long-term follow-up. The fecal microbiome profile was accessed via 16S rRNA sequencing before and after FMT. Results: After the first FMT, 22.58% (7/31) of patients achieved clinical remission and endoscopy remission, with the clinical response rate of 67.74% (21/31), which increased to 55% (11/20) and 80% (16/20), respectively, after the second FMT. No serious adverse events occurred in all patients. During 4 years of follow-up, the mean remission period of patients was 26.5 ± 19.98 m; the relapse rate in the 12 remission patients was 33.33% within 1 year, and 58.3% within 4 years. At baseline, UC patients showed an enrichment in some proinflammatory microorganisms compared to the donor, such as Bacteroides fragilis, Clostridium difficile, and Ruminococcus gnavus, and showed reduced amounts of short-chain fatty acid (SCFA) producing bacteria especially Faecalibacterium prausnitzii. FMT induced taxonomic compositional changes in the recipient gut microbiota, resulting in a donor-like state. Given this specific donor, UC recipients with different outcomes showed distinct gut microbial features before and after FMT. In prior to FMT, relapse was characterized by higher abundances of Bacteroides fragilis and Lachnospiraceae incertae sedis, together with lower abundances of Bacteroides massiliensis, Roseburia, and Ruminococcus; Prevotella copri was more abundant in the non-responders (NR); and the patients with sustained remission (SR) had a higher abundance of Bifidobacterium breve. After FMT, the NR patients had a lower level of Bifidobacterium compared to those with relapse (Rel) and SR, while a higher level of Bacteroides spp. was observed in the Rel group. Conclusion: Low-intensity single donor FMT could induce long remission in active UC. The gut microbiota composition in UC patients at baseline may be predictive of therapeutic response to FMT.